Perancangan Aplikasi Data Mining Penjualan Laptop Pada Sinergi Komputer Lubuklinggau Menggunakan Algoritma C 4.5 - Budi Santoso (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
CV Sinergi Komputer is a store selling computer equipment in the city of Lubuklinggau, Location of CV Sinergi Komputer on Jl. Yos Sudarso No.162 Marga Mulya Village, Lubuklinggau Selatan II Subdistrict, Lubuklinggau City. This company provides many laptops for sale to consumers, laptop sales transactions are very much on the CV Sinergi Computers, consumers who buy laptops on Sinergi Computer there are from outside the city Lubuklinggau, Musi Rawas District and North Musi Rawas District. The problem faced by the CV management is the structure of the presentation of data used in the company is still difficult to do analysis. The problem is caused by the existing system does not support in the analysis needs because the system is only used for operational needs. To perform the process of analysis of the number of laptop sales transactions, the management must review the results of transactions using Microsoft Excel to be able to get a lot of information from different sources. Management believes that it is still not effective because the analysis process is done conventionally using Microsoft Office Excell and require a long process that inhibits the efficiency of time, it takes a multidimensional concept that is able to provide convenience in obtaining strategic information to obtain the right results in determining the analysis of data Will later become a reference in decision making.